Paths to a middle ground : the diplomacy of Natchez, Boukfouka, Nogales, and San Fernando de las Barrancas, 1791-1795 - Weeks, Charles A., 1937- (University of Alabama Press, 2005)
Charles Weeks explores the diplomacy of Spanish colonial officials in New Orleans and Natchez in order to establish posts on the Mississippi River and Tombigbee rivers in the early 1790s. Another purpose of this diplomacy, urged by Indian leaders and embraced by Spanish officials, was the formation of a regional Indian confederation that would deter American expansion into Indian lands. Weeks shows how diplomatic relations were established and maintained in the Gulf South between Choctaw, Chickasaw, Creek, and Cherokee chiefs and their Spanish counterparts aided by traders who had become integr.
Keywords: Natchez Region (Miss.) -- Ethnic relations.; Mobile Region (Ala.) -- Ethnic relations.; Tombigbee River Region (Miss. and Ala.) -- Ethnic relations.; Indians of North America -- Government relations -- 1789-1869.; Spaniards -- Mississippi -- Natchez -- History -- 18th century.; Spaniards -- Louisiana -- New Orleans -- History -- 18th century.; Colonial administrators -- Mississippi -- Natchez -- History -- 18th century.; Colonial administrators -- Louisiana -- New Orleans -- History -- 18th century.; Political culture -- Mississippi -- Natchez Region -- History -- 18th century -- Sources.; Political culture -- Alabama -- Mobile Region -- History -- 18th century -- Sources.; Peuples autochtones -- États-Unis -- Relations avec l'État -- 1789-1869.; Espagnols -- Mississippi -- Natchez -- Histoire -- 18e siècle.; Espagnols -- Louisiane -- La Nouvelle-Orléans -- Histoire -- 18e siècle.; Administrateurs coloniaux -- Mississippi -- Natchez -- Histoire -- 18e siècle.; Administrateurs coloniaux -- Louisiane -- La Nouvelle-Orléans -- Histoire -- 18e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Ethnic Studies -- General.; SOCIAL SCIENCE -- Minority Studies.; Colonial administrators; Ethnic relations; Indians of North America -- Government relations; Political culture; Spaniards; Alabama -- Mobile Region; Louisiana -- New Orleans; Mississippi -- Natchez; Mississippi -- Natchez Region; Diplomatie; Natchez, Miss. -- Region; New Orleans, La.; Spanier.; Indianer.; 1700-1869; History; Sources